CONCORDANCE OF THE SCORING SYSTEM AND GENE-XPERT MTB/RIF TO DIAGNOSE CHILDHOOD TUBERCULOSIS IN PRIMARY HEALTH CARE - Zeffira, Laura; Finny Fitry Yani; Rizanda Machmud (Sean Institute, 2022)
The Scoring system developed by the Indonesian childhood tuberculosis working group is an alternative way to clinically diagnose TB in children especially in primary health care, however, bacteriological confirmation using gene-Xpert MTB/RIF is still highly recommended. To compare childhood TB scoring system performance and gene-Xpert MTB/RIF results among children suspected of tuberculosis in primary health care. This study was conducted on 47 children who went to the primary health care facility. The design of this study was a cross-sectional study with a conformity test (kappa). Samples that meet the inclusion criteria are recorded in the form of age, gender, weight, height, nutritional status, previous history of BCG vaccination, and physical examination, then the data is entered into the scoring system. Sputum is obtained by induction and then examined using gene-Xpert. The number of boys and girls suspected of having pulmonary TB is almost the same. About 72% of children experience malnutrition and a positive BCG score is found in more than half of the samples. There were 51.1% of children in contact with positive smear adult TB patients. Based on the scoring system obtained a TB diagnosis of 74.5% whereas based on gene-Xpert MTB/RIF examination only 4.3% of children confirm TB. There is no match between the two (conformity test with the kappa values of -0.01 and suitability 0.397). There is no compatibility in making a diagnosis of pediatric tuberculosis between the scoring system and gene-Xpert MTB/RIF at the primary health care facility.